Return to Sports and Recurrences After Arthroscopic Anterior Shoulder Stabilization in Martial Arts Athletes. Issue 9 (13th September 2017) - Ranalletta, Maximiliano; Rossi, Luciano A.; Sirio, Adrian; Diaz Dilernia, Fernando; Bertona, Agustin; Maignon, Gastón D.; Bongiovanni, Santiago L.
Background: The high demands to the glenohumeral joint and the violent shoulder blows experienced during martial arts (MA) could compromise return to sports and increase the recurrence rate after arthroscopic stabilization for anterior shoulder instability in these athletes. Purpose: To report the functional outcomes, return to sports, and recurrences in a series of MA athletes with anterior shoulder instability treated with arthroscopic stabilization with suture anchors. Study Design: Case series; Level of evidence, 4. Methods: A total of 20 consecutive MA athletes were treated for anterior shoulder instability at a single institution between January 2008 and December 2013. Range of motion (ROM), the Rowe score, a visual analog scale (VAS), and the Athletic Shoulder Outcome Scoring System (ASOSS) were used to assess functional outcomes. Return-to-sport and recurrence rates were also evaluated. Results: The mean age at the time of surgery was 25.4 years (range, 18-35 years), and the mean follow-up was 71 months (range, 36-96 months). No significant difference in preoperative and postoperative shoulder ROM was found. The Rowe, VAS, and ASOSS scores showed statistical improvement after surgery ( P < .001). In all, 19 athletes (95%) returned to sports. However, only 60% achieved ≥90% recovery after surgery. The recurrence rate was 20%. Conclusion: In this retrospective study of a consecutive cohort of MA athletes, arthroscopic anterior shoulder stabilization significantly improved functional scores. However, only 60% of the athletes achieved the same level of competition, and there was a 20% recurrence rate.